Acid-assisted polysaccharides extracted from Asparagus cochinchinensis protect against Alzheimer’s disease by regulating the microbiota-gut-brain axis - Ruixue Li; Hui Wang; Qinjian Wang; Zhiqiang Zhang; Li Wang (Frontiers in Nutrition)
In this study, an acid-assisted extraction strategy was used to extract a novel polysaccharide (ACP) from Asparagus cochinchinensis, after which this polysaccharide was purified and subjected to extensive characterization. ACP was determined to have an average molecular weight of 15,580 Da in structural characterization studies, and it was found to primarily consist of glucose, galactose, L-fucose, and fructose at an 82.14:12.23:2.61:2.49 ratio. Trace amounts of xylose, arabinose, and rhamnose were also detected in ACP preparations at a 0.48:0.04:0.02 ratio. GC–MS analyses identified eight different sugar linkages within ACP, including Glcp-(1→, →2)-Glcp-(1→, →6)-Glcp-(1→, →4)-Glcp-(1→, →3, 4)-Glcp-(1→, →2,4) -Galp-(1→, →4,6)-Galp-(1→, and →3,4,6)-Galp-(1 → linkages present at 23.70:1.30:3.55:50.77:6.91:1.10:11.50:1.18 molar percent ratios. One-dimensional NMR, two-dimensional NMR, and methylation analyses ultimately revealed that the polysaccharide is mainly composed of →4)-β-D-Glcp-(1 → and a small amount→4,6)-α-D-Galp-(1 → and →3,4)-α-D-Glcp-(1 → and so on. Branched chain is mainly composed of α-D-Glcp-(1 → 4)-β-D-Glcp-(1 → connected to the sugar residues α-D-Glcp-(1 → 4)-β-D-Glcp-(1 → O-4 position or sugar residues of α-D-Glcp-(1 → 4)-β-D-Glcp-(1 → O-3 position. ACP treatment in SAMP8 mice was associated with reductions in oxidative stress and brain pathology together with enhanced cognitive function. ACP treated SAMP8 mice also presented with increases in Bacteroidota abundance and reduced Firmicutes, Patescibacteria, Actinobacteriota, and Campilobacterota abundance. Thus, ACP can prevent Alzheimer’s disease by modulating the microbe-gut-brain axis.